Linked Data Application for publishing and retrieving data from mammalian collections - Cosme, Helder M.; Medeiros, Adriana P. de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Several research institutions have collections of mammals, which are biological collections that contain important data about the species present in a given region. However, they face problems related to the management of this data and its dissemination, since in many cases this data is stored in spreadsheets, which makes data access and disclosure difficult. This work presents an application that uses the principles of Linked Data and the Darwin Core standard to publish the data of the mammalian collections. It allows accessing data in a friendly way and obtaining more related data, present in other repositories, in order to enrich the data of the samples of species of a collection.